Vibrational dependence of line coupling and line mixing in self-broadened parallel bands of NH3. (December 2017) - Ma, Q.; Boulet, C.; Tipping, R.H.
Abstract: Line coupling and line mixing effects have been calculated for several self-broadened NH3 lines in parallel bands involving an excited ν2 mode. It is well known that once the ν2 mode is excited, the inversion splitting quickly increases as this quantum number increases. In the present study, we have shown that the ν2 dependence of the inversion splitting plays a dominant role in the calculated line-shape parameters. For the ν2 band with a 36 cm −1 splitting, the intra-doublet couplings practically disappear and for the 2ν2 and 2ν2 - ν2 bands with much higher splitting values, they are completely absent. With respect to the inter-doublet coupling, it becomes the most efficient coupling mechanism for the ν2 band, but it is also completely absent for bands with higher ν2 quantum numbers. Because line mixing is caused by line coupling, the above conclusions on line coupling are also applicable for line mixing. Concerning the check of our calculated line mixing effects, while the present formalism has well explained the line mixing signatures observed in the ν1 band, there are large discrepancies between the measured Rosenkranz mixing parameters and our calculated results for the ν2 and 2ν2 bands. In order to clarify these discrepancies, we propose to make some new measurements. In addition, we have calculated self-broadened half-widths in the ν2 and 2ν2 bands and made comparisons with several measurements and with the values listed in HITRAN 2012. In general, the agreements with measurements are very good. In contrast, the agreement with HITRAN 2012 is poor, indicating that the empirical formula used to predict the HITRAN 2012 data has to be updated. Highlights: New formalism is applied to calculate line shape parameters in parallel bands of NH3 . Theoretical results are compared with measurements in the ν2, 2ν2, and 2ν2 -ν2 bands. Half-widths and line mixing parameters strongly depend on excitation of the ν2 mode.